2020
DOI: 10.1016/j.psj.2019.10.036
|View full text |Cite
|
Sign up to set email alerts
|

Effects of encapsulated cinnamaldehyde and citral on the performance and cecal microbiota of broilers vaccinated or not vaccinated against coccidiosis

Abstract: This study investigated the effects of encapsulated cinnamaldehyde ( CIN ) and citral ( CIT ) alone or in combination ( CIN + CIT ) on the growth performance and cecal microbiota of nonvaccinated broilers and broilers vaccinated against coccidiosis. Vaccinated (1,600) and nonvaccinated (1,600) 0-day-old male Cobb500 broilers were randomly allocated to 5 treatments: basal diet (control) and basal diet supplemented with bacitracin ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 90 publications
3
49
0
Order By: Relevance
“…[246], and Streptococcus pyogenes [247]. In this context, Yang and colleagues recently demonstrated that when combined with cinnamaldehyde, citral changed cecal microbiota composition of non-vaccinated and vaccinated broiler chickens, reducing the incidence and severity of necrotic enteritis induced by coccidiosis [239]. This is in accordance with another finding, in which citral was able to affect mouse intestinal microbiota, enhancing the relative abundance of Lactobacillus [108].…”
Section: Citralsupporting
confidence: 66%
See 1 more Smart Citation
“…[246], and Streptococcus pyogenes [247]. In this context, Yang and colleagues recently demonstrated that when combined with cinnamaldehyde, citral changed cecal microbiota composition of non-vaccinated and vaccinated broiler chickens, reducing the incidence and severity of necrotic enteritis induced by coccidiosis [239]. This is in accordance with another finding, in which citral was able to affect mouse intestinal microbiota, enhancing the relative abundance of Lactobacillus [108].…”
Section: Citralsupporting
confidence: 66%
“…Citral, (2E)-3,7-dimethylocta-2,6-dienal, is the main compound of essential oils that have been used mainly in popular medicine in eastern countries. It is the major compound extracted from Cymbopogon citratus, popularly known as lemongrass, but it can also be extracted from different plants including lemon myrtle and Lindera citriodora [239]. This essential oil has been used as ingredient in foods because of its lemon-like fragrance.…”
Section: Citralmentioning
confidence: 99%
“…Birds were managed according to the Cobb recommendations (Cobb Breeder Management Guide and Vantress.com). The composition of the starter (days 0–10), grower (days 10–20), and finisher (days 20–30) diets included corn as the principal cereal, and soya and soybean cake as protein concentrates to meet the nutrient requirements for broiler Cobb-500 ( 20 , 21 ).…”
Section: Methodsmentioning
confidence: 99%
“…Chicks were weighed at the start of the trial (day 0) and every week thereafter. Performance parameters including BW, feed intake (FI), and FE were measured at days 10 (phase 1), 20 (phase 2), and 30 (phase 3) from each pen ( 20 ). Birds were inspected at least twice daily.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation